2016
DOI: 10.1039/c6fo00244g
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinus officinalis L. extract ameliorates intestinal inflammation through MAPKs/NF-κB signaling in a murine model of acute experimental colitis

Abstract: We investigated the anti-inflammatory and anti-colitis effects of Rosmarinus officinalis L. extract (RE) by using both in vitro LPS-activated mouse RAW 264.7 macrophages and in vivo dextran sulfate sodium (DSS)-induced experimental murine colitis and suggested the underlying possible mechanisms. Liquid Chromatography-Mass Spectrometry (LC-MS) analysis was performed to identify the major components present in the RE. The clinical signs, biochemistry, immunoblot, ELISA and histology in colon tissues were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Medicherla et al suggested that R. officinalis extract (50 and 100 mg/kg) attenuated COX-2 and inducible nitric oxide synthase expressions, TNF-α and IL-6 levels, and myeloperoxidase activity in dextran sulfate sodium-induced experimental murine colitis. Moreover, they reported that R. officinalis extract decreases the LPS-induced inflammatory cytokine production and inflammatory protein expression in LPS-activated mouse RAW 264.7 macrophages [19]. These studies confirmed our results regarding the anti-inflammatory effects of R. officinalis extract.…”
Section: Discussionsupporting
confidence: 91%
“…Medicherla et al suggested that R. officinalis extract (50 and 100 mg/kg) attenuated COX-2 and inducible nitric oxide synthase expressions, TNF-α and IL-6 levels, and myeloperoxidase activity in dextran sulfate sodium-induced experimental murine colitis. Moreover, they reported that R. officinalis extract decreases the LPS-induced inflammatory cytokine production and inflammatory protein expression in LPS-activated mouse RAW 264.7 macrophages [19]. These studies confirmed our results regarding the anti-inflammatory effects of R. officinalis extract.…”
Section: Discussionsupporting
confidence: 91%
“…TNF-α-induced phosphorylation of AKT is significantly suppresses in HT-29 colonic epithelial cells by 7- O -succinyl macrolactin A in parallel to inhibition of NF-κB translocation [38]. In murine models of DSS Rosmarinus officinalis extract ameliorates intestinal inflammation through MAP kinases/NF-κB signaling [39]. It is also known that expression of the novel adipokine CTRP4 suppresses colitis in mice with a marked downregulation of ERK, AKT and STAT3 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evaluation of the severity of the disease was estimated using the procedure by Medicherla et al The disease activity index was estimated according to the observation of score which is allocated for each disease symptoms, including fluctuation of body weight, consistency of defecation and occurrence of bloody stool (fecal bleeding) and the presence of occult blood by a guaiac test.…”
Section: Methodsmentioning
confidence: 99%